(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
An article in the Kenyan newspaper, "Daily Nation" of 27th January 2000 page 5, under the heading "Council Opposes AIDS Vaccine Trials" caught my attention. It referred to an impending clinical trial of HIV vaccine developed jointly by British and Kenyan immunologists. It is currently undergoing phase I clinical trials in Oxford, England and is scheduled to undergo phase II trials in Kenya, starting in July, 2000. In the article the All African Council of Churches (AACC) General Secretary, Rev. Canon C.J. was quoted as having warned against the complications and ethical problem that could follow the planned HIV vaccine trials in Kenya